2023
DOI: 10.3390/jcm12237353
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of the Baseline and Early Changes in Monocyte-to-Lymphocyte Ratio for Short-Term Mortality among Critically Ill Patients with Acute Kidney Injury

Xinyao Luo,
Dingyuan Wan,
Ruoxin Xia
et al.

Abstract: (1) Background: Inflammation plays an important role in the onset and progression of acute kidney injury (AKI). Despite this, evidence regarding the prognostic effect of the monocyte-to-lymphocyte ratio (MLR), a novel systemic inflammation marker, among patients with AKI is scarce. This study sets out to investigate the prognostic potential of both baseline and early changes in MLR for short-term mortality among critically ill patients with AKI. (2) Method: Eligible patients with AKI from the Medical Informati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…The neutrophil-to-lymphocyte ratio, platelet-to-lymphocyte ratio, and MLR are indicators of these immune cells. Numerous studies have demonstrated that these markers can predict the presence of systemic inflammation and may be helpful in the diagnosis of various disorders ( 8 , 20 , 21 , 31 ). Recently, some studies have shown that the high MLR is associated with the occurrence and progression of diabetes complications, including diabetic nephropathy, DR, and PAD ( 7 , 22 24 , 32 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The neutrophil-to-lymphocyte ratio, platelet-to-lymphocyte ratio, and MLR are indicators of these immune cells. Numerous studies have demonstrated that these markers can predict the presence of systemic inflammation and may be helpful in the diagnosis of various disorders ( 8 , 20 , 21 , 31 ). Recently, some studies have shown that the high MLR is associated with the occurrence and progression of diabetes complications, including diabetic nephropathy, DR, and PAD ( 7 , 22 24 , 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been widely studied in various inflammation-related disorders, such as cancer, tuberculosis and cardiovascular diseases, and has proven to be a reliable biomarker of systemic inflammation ( 17 19 ). Elevated MLR has been associated with poor prognosis and accelerated disease progression in several disorders, including acute kidney injury and hematoma after cerebral contusion ( 20 , 21 ). Recently, some studies have shown that the MLR is associated with the occurrence and progression of diabetes complications, including diabetic nephropathy, diabetic retinopathy (DR), and PAD ( 7 , 22 24 ).It is reasonable to assume that MLR may play a significant role in the onset and progression of DFU, given the mounting body of research emphasizing its importance in diabetes complications ( 7 , 22 24 ).…”
Section: Introductionmentioning
confidence: 99%